Peran Kepemimpinan Teman Sejawat Dalam Membangun Solidaritas Dan Keputusan Bersama - Fashli Fajar; Muhammad Farhan Merdwinsyah; Nayla Dhea Pratiwi; Nur Azizi; Nurul Afri Dewi; Riska Aulia Putri; Sintia Revita; Syamsir . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role of peer leadership in fostering solidarity and supporting collective decision-making within student organizations. This study employed a qualitative approach using descriptive methods and was conducted at the Student Association of the Department of Public Administration, Padang State University. Data were collected through in-depth interviews with five informants consisting of organizational administrators and active student members. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The problems identified in this study include miscommunication, differences of opinion, individual ego, and varying levels of member participation that may affect the effectiveness of student organizations in building solidarity and collective decision-making. The findings show that leadership in student organizations is not only formal but also develops informally through interactions among members. Peer leadership plays an important role in improving communication, participation, cooperation, and solidarity among organizational members. In addition, decision-making processes are carried out through participatory deliberation and discussion involving members actively. This study also reveals that effective communication and positive interpersonal relationships can improve organizational effectiveness and strengthen members’ sense of collective responsibility. Therefore, peer leadership has a strategic role in strengthening solidarity and supporting democratic, inclusive, and participatory decision-making processes within student organizations.